Corpus d'apprenants et acquisition des langues - Sylvie De Cock; Henry Tyne (Recherches en didactique des langues et des cultures)
Learner corpora are systematic "electronic collections of spoken or written texts produced by foreign or second language learners" (Granger, 2004: 124). These corpora have been used to explore specific aspects of second language acquisition. The first section of this paper illustrates the insights into L2 development that can be gained from learner corpus research. The second section presents and discusses possible pedagogical applications of this type of research. The article then offers a more critical perspective on learner corpus research and more generally on studies on second language acquisition and the use of corpora in language research.